High activation of STAT5A drives peripheral T-cell lymphoma and leukemia - Maurer, Barbara; Nivarthi, Harini; Wingelhofer, Bettina; Pham, Ha Thi Thanh; Schlederer, Michaela; Suske, Tobias; Grausenburger, Reinhard; Schiefer, Ana-Iris; Prchal-Murphy, Michaela; Chen, Doris; Winkler, Susanne; Merkel, Olaf; et al. (Haematologica, 2020)
Recurrent gain-of-function mutations in the transcription factors STAT5A and much more in STAT5B were found in hematopoietic malignancies with the highest proportion in mature T- and natural killer-cell neoplasms (peripheral T-cell lymphoma, PTCL). No targeted therapy exists for these heterogeneous and often aggressive diseases. Given the shortage of models for PTCL, we mimicked graded STAT5A or STAT5B activity by expressing hyperactive Stat5a or STAT5B variants at low or high levels in the hematopoietic system of transgenic mice. Only mice with high activity levels developed a lethal disease resembling human PTCL. Neoplasia displayed massive expansion of CD8+ T cells and destructive organ infiltration. T cells were cytokine-hypersensitive with activated memory CD8+ T-lymphocyte characteristics. Histopathology and mRNA expression profiles revealed close correlation with distinct subtypes of PTCL. Pronounced STAT5 expression and activity in samples from patients with different subsets underline the relevance of JAK/STAT as a therapeutic target. JAK inhibitors or a selective STAT5 SH2 domain inhibitor induced cell death and ruxolitinib blocked T-cell neoplasia in vivo We conclude that enhanced STAT5A or STAT5B action both drive PTCL development, defining both STAT5 molecules as targets for therapeutic intervention.
Keywords: cytokiny; myši; CD8-pozitivní T-lymfocyty; nádorové supresorové proteiny; Lymphoma, T-Cell, Peripheral; zvířata; Humans; Mice; Cytokines; periferní T-buněčný lymfom; CD8-Positive T-Lymphocytes; STAT5 Transcription Factor; leukemie; Leukemia; Tumor Suppressor Proteins; lidé; transkripční faktor STAT5; Animals